Inequality of opportunity: the plight of foreign workers in South Africa - Biney, Elizabeth (Institute of Development and Labour Law, 2017)
Migration can be a hazardous venture, particularly if carried out clandestinely. Evidence indicates that foreigners working without formal authorisation, i.e. 'irregular migrant workers', are in a particularly vulnerable position primarily because of their irregular immigration status. They are more likely to be subjected to exploitative and unsafe employment practices in terms of benefits and conditions. This study examines the protection available to this category of migrant workers in South Africa, particularly their right of access to work-related social protection. South Africa is a major migrant-receiving country in Southern Africa because of its relatively stronger economy and political stability. However, the employment of foreign nationals without work permits, or foreigners working contrary to visa requirements, raises a series of policy issues. These issues, against the background of fairness and equity discourses pertaining to socio-economic entitlements, become exacerbated. This study examines the adequacy of domestic, constitutional and legislative frameworks that offer work-related social protection to foreign workers in South Africa. In the context of international, continental, and regional instruments that provide similar protection to irregular migrants, it could be argued that South Africa's restrictive legislative framework compromises equality in the right of access to social protection for some migrants. Although effective migration management depends on careful juxtaposition of myriad policies, emerging evidence suggests conflicting interplay between key South African policies intended to manage the rights of workers specifically and labour migration in the country generally. Critical analysis of relevant national immigration, labour, and social security laws indicates inconsistency with international human rights principles concerning the equality of opportunity or treatment of irregular migrants vis-àvis regular migrants and nationals regarding social protection. Yet, inequalities in the actual processes or opportunities (means) embedded in these policies disentitle many vulnerable foreign workers from important constitutionally entrenched fundamental rights because their presence and/or employment violates existing immigration laws. The study concludes by recommending policy interventions that may help remedy these problems.